PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA MARTABAK BANGKA PINANG SEBATANG - Siti Nur Haliza Oktavia; Dadan Abdul Aziz Mubarok; Rama Chandra Jaya (IKRAITH-EKONOMIKA, 2025)
This study aims to investigate the extent to which product quality and service quality influence customer satisfaction at Martabak Bangka Pinang Sebatang. The research employed a quantitative approach, utilizing a survey technique as the main instrument for data collection. Primary data were gathered from 100 respondents who had previously made purchases, selected using a reasoned sampling method. The dataset was subsequently examined through multiple linear regression analysis, assisted by SPSSversion 27. The empirical results indicate that product quality emerges as a dominant determinant of customer satisfaction, supported by a significance level below 0.001 and a t-statistic of 8.472, reflecting a robust statistical relationship. In parallel, service quality was also found to have a statistically significant and positive effect on customer satisfaction, as demonstrated by a significance value of 0.004 and a t-value of 2.964. Moreover, when both independent variables were analyzed concurrently, product quality and service quality collectively exhibited a significant impact on customer satisfaction, as evidenced by an F-value of 39.711 and an R² value of 0.461. These findings underscore that systematic enhancement of both product quality and service quality constitutes a crucial strategic foundation for improving customer satisfaction and reinforcing competitive positioning within the culinary business sector